2012
DOI: 10.1089/jwh.2011.2766
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Adverse Birth Outcomes Among Socially Disadvantaged Women

Abstract: Background: Numerous studies find that socially disadvantaged women are more likely than socially advantaged women to deliver infants that weigh less than normal and/or are born weeks prior to their due date. However, little is known about the pathways that link maternal social disadvantage to birth outcomes. Using data from a prospective cohort study, we examined whether antenatal psychosocial stress, substance use, and maternal health conditions in pregnancy mediated the pathway between maternal social disad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…Prenatal stress (PS) has also been tied to attention deficits (Li et al, 2010; Rodriguez and Bohlin, 2005; Wilson et al, 2012) that can include heightened impulsivity (Grizenko et al, 2008). This concurrence of outcomes is notable, given that the greatest proportion of children with elevated blood lead (PbB) levels reside in low socioeconomic status communities, where prenatal stress is also considered to be highly prevalent (Gavin et al, 2012; Lancaster et al, 2010; Miszkurka et al, 2012), consistent with the interpretation that these are co-occurring risk factors in the human environment. That elevated PbB levels and PS should lead to common adverse outcomes including cognitive and attention deficits, likely reflects the fact that both Pb exposure and prenatal stress also significantly modify the functions of the central nervous system’s (CNS) fronto-striatal/mesocorticolimbic circuits, and its associated monoamine (dopamine and serotonin)-glutamate balance (Barros et al, 2004; Berger et al, 2002; Cory-Slechta et al, 1998; 1999; Martinez-Tellez et al, 2009; Rossi-George et al, 2011; Virgolini et al, 2008), that have been shown to subserve these behavioral domains (Dalley et al, 2008; Dalley and Roiser, 2012; Kim and Lee, 2011; Luman et al, 2010; Pattij and Vanderschuren, 2008; Tripp and Wickens, 2009).…”
Section: Introductionmentioning
confidence: 71%
“…Prenatal stress (PS) has also been tied to attention deficits (Li et al, 2010; Rodriguez and Bohlin, 2005; Wilson et al, 2012) that can include heightened impulsivity (Grizenko et al, 2008). This concurrence of outcomes is notable, given that the greatest proportion of children with elevated blood lead (PbB) levels reside in low socioeconomic status communities, where prenatal stress is also considered to be highly prevalent (Gavin et al, 2012; Lancaster et al, 2010; Miszkurka et al, 2012), consistent with the interpretation that these are co-occurring risk factors in the human environment. That elevated PbB levels and PS should lead to common adverse outcomes including cognitive and attention deficits, likely reflects the fact that both Pb exposure and prenatal stress also significantly modify the functions of the central nervous system’s (CNS) fronto-striatal/mesocorticolimbic circuits, and its associated monoamine (dopamine and serotonin)-glutamate balance (Barros et al, 2004; Berger et al, 2002; Cory-Slechta et al, 1998; 1999; Martinez-Tellez et al, 2009; Rossi-George et al, 2011; Virgolini et al, 2008), that have been shown to subserve these behavioral domains (Dalley et al, 2008; Dalley and Roiser, 2012; Kim and Lee, 2011; Luman et al, 2010; Pattij and Vanderschuren, 2008; Tripp and Wickens, 2009).…”
Section: Introductionmentioning
confidence: 71%
“…Such chronic conditions would compromise women's chances of delivering a healthy infant even before they conceive the pregnancy (Geronimus, Andersen, & Bound, 1991;Hogue & Bremner, 2005). Also, as a response to chronic stress, women may adopt or reinforce behavioral coping mechanisms, such as smoking, drinking, or late PNC (Gavin, Nurius, & Logan-Greene, 2012;Myers, 2009), which can elevate their adverse birth risks. Among these biomedical and behavioral pathways, hypertension and smoking have repeatedly suggested to explain weathering and the underlying chronic stress mechanism among racial/ethnic minority women (Geronimus, 1996;Holzman et al, 2009;Khoshnood, Wall, & Lee, 2005;Powers, 2013;Rich-Edwards et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Women who have experienced significant adversities during childhood (e.g., abuse) and adulthood (e.g., poverty or low socioeconomic conditions) are at risk for excessive inflammation, which has implications for pregnancy (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016). A history of childhood exposure to abuse and low socioeconomic status (SES) have been independently associated with a chronic inflammatory state characterized by elevations in inflammatory markers across the lifespan (Azad et al, 2012; Baumeister et al, 2016; Danese et al, 2007; Pollitt et al, 2008), in addition to adverse pregnancy outcomes characterized by excessive inflammation (Bushnik et al, 2017; Gavin et al, 2012; Silva et al, 2008; Smith et al, 2016). However, it is still unclear how chronic adversities experienced during childhood and adulthood affect inflammatory states in pregnant women.…”
Section: Introductionmentioning
confidence: 99%